A RE-EVALUATION OF THE SYSTEMATICS AND MORPHOLOGY OF CERTAIN ANOMODONT THERAPSIDA - Keyser, A. W. (My University, 1972)
The cranial morphology of a number of specimens assigned to the genera Oudenodon, Rhachiocephalus, Aulacephalodon and Pelanomodon was investigated (Keyser, 1969). It was found that the internal morphology and the general structure of the skulls show great agreement. Many of the differences between the genera can be associated with the size of the skull. The main differences between the genera lie in the specialisation of the biting mechanism and in the relative size and shape of the nasal and prefrontal bosses. It is suggested that the genera Oudenodon and Rhachio cephalus bit off their food with the sides of the horn-covered jaws while the broadnosed genera Aulacephalodon and Pelanomodon bit with the transverse anterior tips of the jaws. This difference in the morphology of the jaws is probably indicative of a fundamental dichotomy between the two groups of genera. A similar dichotomy has been suggested for Triassic dicynodonts by Cox (1965).